New, Efficient Approach for the Ligand-Free Suzuki–Miyaura Reaction of 5-Iodo-2′-deoxyuridine in Water - Sartori, Guillaume; Hervé, Gwénaëlle; Enderlin, Gérald; Len, Christophe (Synthesis, 2013)
A series of 5-aryl-2′-deoxyuridines was prepared, using ligandless Suzuki–Miyaura cross-coupling reactions in neat water, starting from 5-iodo-2′-deoxyuridine as totally deprotected starting material. This ligand-free process gave good to high isolated yields within short reaction times and with low loadings of palladium.
Keywords: Suzuki–Miyaura reaction; ligandless; nucleosides; green chemistry